The Effect of Experience, Work Supervision and Career Development on Job Satisfaction - Ella Anastasya Sinambela; Siti Nur Halizah; Shohibatun Naufalia; Farra Nur Amelia; Samsul Arifin; Didit Darmawan; Arif Rachman Putra (Institute of Advanced Knowledge and Science, 2023)
Job satisfaction is an employee attitude that must be observed by every user of human resources as an organizational mover. This is important to do so that workers get satisfaction and feel that their expectations for the organization can be fulfilled. Factors that cause job satisfaction must be analyzed in order to become the basis of company policy. This study intends to determine the role of work experience, supervision, and career development on job satisfaction. The population in this study are workers in one of the companies in the city of Gresik with a total of 76 people. The sampling technique uses saturated sampling. The analysis technique used in this research is multiple linear regression test. This study concludes that all variables have a partial and simultaneous significant effect on job satisfaction variables. Experience, supervision and career development can be used to develop worker satisfaction. This is expected by every leader so that a leader needs to understand what must be done to create employee job satisfaction. Leaders should always consider the policies made, taking into account the aspects that give rise to employee job satisfaction.